DECISION SUPPORT SYSTEM FOR BOARDING HOUSE RECOMMENDATIONS AROUND UPY BASED ON RULES AND SPATIAL WEB - Ganang Prihatma Artha; Muhammad Fairuzabadi; Aditya Wahana (JTH: Journal of Technology and Health, 2024)
Boarding houses, often referred to simply as "boarding houses," are essential for students studying away from their hometowns. These students seek temporary accommodations to serve as their domicile until they complete their education. When searching for a boarding house, students typically rely on recommendations from local residents or acquaintances living near the campus. Choosing a place to live in a new area involves several factors, including cost, distance, facilities, and the surrounding environment. A Decision Support System (DSS) can assist in this process by providing recommendations that match the desired criteria, making it easier for students to find suitable accommodations. A Rule-Based System is a structured decision-making method that utilizes IF-THEN rules to evaluate various criteria relevant to boarding house selection. By integrating a Decision Support System with Rule-Based Systems and Spatial Web technologies, this approach effectively assists UPY students in finding suitable boarding houses. The system provides comprehensive information and tailored recommendations based on the specific preferences of students or boarding house seekers.